Edge magic total labeling of lexicographic product C4(2r+1) o K2 cycle with chords, unions of paths, and unions of cycles and paths - Inne Singgih (Indonesian Combinatorial Society (InaCombS), 2018)
An edge magic total (EMT) labeling of a graph G = (V, E) is a bijection from the set of vertices and edges to a set of numbers defined by λ : V ∪ E → 1, 2, ..., ∣V∣ + ∣E∣ with the property that for every xy ∈ E, the weight of xy equals to a constant k, that is, λ(x) + λ(y) + λ(xy) = k for some integer k. In this paper given the construction of an EMT labeling for certain lexicographic product C_4(2r+1)° K_2, cycle with chords [c]tCn, unions of paths mPn, and unions of cycles and paths m(Cn1(2r + 1) ∪ (2r + 1)Pn2).